Evaluation of changes in liver function test in first, second and third trimester of normal pregnancy - Gohel, Mukesh G.; Joshi, Anant G.; Anand, Jitendra S.; Makadia, Jemil S.; Kamariya, Chandrakant P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Understanding of physiological adaptations of normal pregnancy remains a major goal of obstetrics, and without such knowledge, it is almost impossible to understand disease processes that can threaten women during pregnancy. Aim of this study is to evaluate changes in serum liver function tests in normal pregnant women in first, second and third trimester. Methods: A hospital based cross sectional in vitro study conducted at Civil Hospital, Ahmedabad (India). A study consists of 150 pregnant women and 50 matched control. Among the 150 pregnant women, 50 were in first trimester, 50 were in second trimester and 50 were in third trimester. Serum sample was taken and assessed for routine liver function tests. Results: Serum total and direct bilirubin concentrations were significantly lower in second and third trimester. Serum ALT and AST activity was slightly but significantly increased in third trimester. Serum ALP activity was significantly higher in second and third trimester. ALP activity increases as pregnancy advances. Serum GGT values were significantly lowers in third trimester. No significant change in serum total proteins concentration, but serum albumin concentration was significantly lower and serum globulin concentration was significantly higher in all three trimester. Serum albumin/globulin ratio was significantly reduced in second and third trimester. Conclusion: Such changes in in liver function tests during normal pregnancy can be misinterpreted as pathological and can also unmask or worsen preexisting disease. So the identification and understanding of these physiological changes in pregnancy is important for the diagnosis of liver diseases during pregnancy.